Preventability of drug-related harms - part I: a systematic review. - Ferner, R; Aronson, J (2010)
'Preventability' is a crucial concept in the literature on adverse drug reactions (ADRs). We have carried out a systematic review in order to identify and analyse the approaches used to define 'preventability' in relation to ADRs. We have restricted this investigation to definitions of preventability and have not dealt with other aspects. We searched MEDLINE (1963-April 2009) and EMBASE (1980-April 2009), without language restriction, for papers in which preventability of ADRs was likely to be defined. We found 234 papers, of which we retrieved 231. Of these, 172 either contained original definitions of preventability or referred to other papers in which preventability was defined. Forty contained no definition, and 19 were not relevant. In the 172 papers selected, we identified eight different general approaches to defining the preventability of ADRs: (1) analysis without explicit criteria; (2) assessment by consensus; (3) preventability linked to error; (4) preventability linked to standards of care; (5) preventability linked to medication-related factors; (6) preventability linked to information technology; (7) categorization of harmful treatments in explicit lists; and (8) a combination of more than one approach. These approaches rely on two general methods: the judgement of one or more investigators or the use of pre-defined explicit criteria; neither is satisfactory. Specific problems include the weakness of consensus as a method (since experts can agree and yet be wrong), inadequacy of definition of standards of care, and circularity in several definitions of preventability. Furthermore, attempts to list all preventable effects are bound to be incomplete and will not always apply to an individual case. We conclude that an approach based on analysis of the mechanisms of adverse reactions and their clinical features could be preferable; such an approach is described in a companion paper (Part II) in this issue of Drug Safety.